The effect of ciprofloxacin on the susceptibility of pseudomonas aeruginosa to tetracycline - Ning Rintiswati, Ning Rintiswati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1998)
The effect of ciprofloxacin on the susceptibility of Pseudomonas aeruginosa to tetracycline was evaluated. This study was based on the fact that most bacterial resistance to an antibiotics is under control of genes located on plasmids. Treatment with ciprofloxacin at subminimal inhibitory concentration possibly alter the supercoiled to the relaxed form, so that the plasmids could not be expressed, whereas at the same time the bacterial chromosome would not be affected by the treatment. The aim of this study was to search for possible increase of tetracycline susceptibility of P.aeruginosa, under the influence of ciprofloxacin. Thirty two isolates of P.aeruginosa were used In the experiment. Minimal inhibitory concentration (MIC) of ciprofloxacin for an individual isolate was determined by a standard broth dilution method. Fresh cultures with the density of 106CFU/m1 were added Into a serial tubes containing various concentrations of tetracycline. Ciprofloxacin at sub MICs was then added into these cultures. The same cultures containing only tetracycline were used for controls. The results showed that the decrease of MIC of tetracycline was observed in 31 (96.87%) isolates of P.aeruginosa, and 34.37% changed their resistance stated. It was concluded that ciprofloxacin increased tetracycline susceptibility of P.aeruginosa.Key words : ciprofloxacin - plasmid - antibiotic susceptibility - P. aeruginosa-tetracycline